Peningkatan Ketrampilan Dan Manajemen Pemasaran Usaha Rumahan Penghasil Kue Di Kelurahan Sidomulyo - Sri Rahmayanti; Misral Misral; Siti Hanifa Sandri; Hendri Ali Ardi; Bakaruddin Bakaruddin; Norra Isnasia Rahayu; Jeki Algusri (Asosiasi Dosen Akuntansi Indonesia, 2021)
The cake making business is a home-based business that is widely practiced by people in Pekanbaru. The large demand for cakes is a promising business opportunity. The conditions of intense competition require cake-making businesses to be active in making breakthroughs and innovations, so that their products remain in demand by consumers. The cake-making business as a small business also experiences various obstacles, including low turnover and production capacity, as well as weakness in the marketing aspect, especially in distribution channels for its products. This community service activity is carried out on cake-making entrepreneurs in West Sidomulyo Pekanbaru. This activity aims: 1) cake-producing entrepreneurs can run their business professionally, creatively and innovatively, 2) expand the market for their products, 3) increase their production capacity, 4) increase their expertise and skills in making sponge cakes. Activities in this service include training in marketing management, entrepreneurship, and preparation of financial reports). Based on the implementation and evaluation of the results of activities, it can be concluded that cake-producing entrepreneurs can run their business professionally, creatively and innovatively, and there is an increase in production capacity due to increased demand from customers.